Sensitivity Test of Betts-Miller-Janjic and Grell-3D Cumulus Schemes on WRF-ARW Model to Simulate the Heavy Rainfall Event in Lampung (Case Study: 20 February 2017) - D Fatmasari; I J A. Saragih; A W Putra; I R Nugraheni (International Conference on Coastal and Delta Areas, 2017)
Lampung is a southernmost province on the island of Sumatra, Indonesia. The occurrence of heavy rain on 20 February 2017 caused flooding in some areas in Lampung. The heavy rain that lasts long enough, from 11:40 UTC to 23:00 UTC, is due to a group of convective clouds that form the Mesoscale Convective Complex (MCC) which observed on Himawari-8 satellite images. Data used in this research are FNL (Final Analysis) data from http://rda.ucar.edu/, Himawari-8 data from BMKG, and GSMaP rainfall data from ftp://hokusai.eorc.jaxa.jp. The aim of this study is to test the sensitivity of two cumulus parameterization schemes of WRF, they are Betts-Miller-Janjic and Grell-3D. Testing is done by using spatial verification and statistical verification. Overall, the output of both schemes shows that the Grell-3D scheme is good enough to describe the occurrence of the heavy rain event. Based on the results of the analysis of both schemes, it is shown that the atmospheric conditions over Lampung are very wet which is indicated by the height of the air moistness in each layer and supported by the convergence area and also the height of CAPE value which supported the formation of convective clouds during this heavy rain event. Keywords: cumulus schemes, WRF-ARW, heavy rain